2015
DOI: 10.18203/2349-2902.isj20150501
|View full text |Cite
|
Sign up to set email alerts
|

Incised surgical wound closure with sutures and staples: a controlled experimental study

Abstract: Background: Development of newer techniques of surgical wound closure which are not associated with contamination. Aim is to evaluate advantages and disadvantages of skin closure with sutures and staples. Methods: A controlled experimental study was conducted on guinea pigs divided into two groups of 10 each in NIMS Medical College, Jaipur, in the year 2013. On 5 th POD signs of inflammation (redness, oedema), discharge (serous/seropurulent/purulent), dehiscence (partial or complete) was assessed. On 15 th POD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[ 8 9 10 ] Many studies showed that initial cosmetic outcome in adhesive tapes was better, but delayed scar widening was not significantly different between sutured wounds and adhesive tapes. [ 6 11 14 15 ] Findings of the present study show that wound tape in comparison to suture in wounds <20 mm was more effective in scar formation, but in wound <50 mm was similar to suture. Hence, these show that wound tape can be used as a suitable wound closure technique in wounds <20 mm.…”
Section: Discussionmentioning
confidence: 58%
“…[ 8 9 10 ] Many studies showed that initial cosmetic outcome in adhesive tapes was better, but delayed scar widening was not significantly different between sutured wounds and adhesive tapes. [ 6 11 14 15 ] Findings of the present study show that wound tape in comparison to suture in wounds <20 mm was more effective in scar formation, but in wound <50 mm was similar to suture. Hence, these show that wound tape can be used as a suitable wound closure technique in wounds <20 mm.…”
Section: Discussionmentioning
confidence: 58%
“…Kochar and Singh reported wound closure with staples was almost three times faster but with less tensile strength of scar tissue than with other types of sutures. 8 Gupta also showed staplers had benefit in terms of less time and expenses consumed. 9 One randomized control trial by Rousse compared staples to subcuticular sutures for cesarean sections abdominal skin closure in 101 women.…”
Section: Discussionmentioning
confidence: 98%